Utilization of Alkane Hydrocarbons in Waste Management to Support a Green Economy Movement for Students - GUSTINA ALFA TRISNAPRADIKA; NOOR AGENG SETIYANTO; SUPRIADI RUSTAD; MULJONO; MUHAMMAD NAUFAL (SWAGATI : Journal of Community Service, 2026)
Household waste management, particularly used cooking oil (waste cooking oil), remains an environmental issue due to low public awareness and limited understanding of sustainable waste management practices. Improper disposal of used cooking oil can lead to environmental pollution and pose health risks. This community service activity aims to improve students’ knowledge and skills in processing used cooking oil into value-added aromatherapy candles, while fostering environmental awareness and an entrepreneurial spirit based on the green economy. The method applied is Community Based Participatory Research (CBPR), conducted in two stages: delivery of theoretical material on the 3R concept (Reduce, Reuse, Recycle) and hands-on practice in processing used cooking oil. The activity was carried out at SMK Negeri 9 Semarang involving 23 students. The results indicate an increase in participants’ understanding, as shown by improvements in scores on 3R education (from 59.5 to 83.3) and used cooking oil processing (from 50 to 85). In addition, students were able to produce aesthetically pleasing aromatherapy candles with economic value potential.